A multivariate study of energy consumption, urbanisation, trade openness and economic growth in Malaysia - Razali, R. (Asian Research Publishing Network, 2015)
This paper investigates both the short and long term dynamic relationships between energy consumption, trade openness, urbanization and economic growth in Malaysia through econometric model during the period of 1971-2013. The novel methodology in econometric techniques such as unit root without structural breaks, co-integration, and vector error correction model (VECM) are being used to analyse the data. Co-integration has been carried out to find long run relationship between the variables. For short run dynamics relationship among the variables, VECM model has been used. The estimated income elasticities indicate that per capita GDP in real term puts a larger influence on energy consumption. The results showed that all variables are stationary at first difference. Also from the empirical results it is evident that there is long run relationships exist among energy consumption and economic growth for the Malaysian economy. Â© 2006-2015 Asian Research Publishing Network (ARPN).